2023
DOI: 10.1002/acp.4051
|View full text |Cite
|
Sign up to set email alerts
|

Strategic offloading: How the value of to‐be‐remembered information influences offloading decision‐making

Abstract: We examined potentially selective offloading decisions when the external store has a limited capacity and how the surprising unavailability of offloaded information influences subsequent offloading decision-making and memory. In three experiments, learners were presented with to-be-remembered words paired with point values counting towards their scores if recalled and were allowed to offload some words.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…While offloading information can increase the total amount of information accessible during recall, there are drawbacks to offloading. For example, if the external store is surprisingly unavailable, information that has been offloaded may be forgotten if it was not sufficiently encoded (see Murphy, 2023a). In Experiment 1, when the external store was surprisingly taken away, both younger and older adults frequently forgot high-value words indicating that these items received less encoding than low-value words which were better recalled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While offloading information can increase the total amount of information accessible during recall, there are drawbacks to offloading. For example, if the external store is surprisingly unavailable, information that has been offloaded may be forgotten if it was not sufficiently encoded (see Murphy, 2023a). In Experiment 1, when the external store was surprisingly taken away, both younger and older adults frequently forgot high-value words indicating that these items received less encoding than low-value words which were better recalled.…”
Section: Discussionmentioning
confidence: 99%
“…Some prior work (primarily using self-report measures) indicates that people are more likely to use external stores to remember things when they are valuable (see Meacham & Singer, 1977; Murphy, 2023a; Penningroth & Scott, 2013). However, it remains unclear how older adults choose what information to offload and if offloaded information is quickly forgotten and not recallable, much like in a directed forgetting task (cf.…”
Section: The Present Studymentioning
confidence: 99%
“…Decisions about cognitive offloading do not always optimize outcomes. Murphy (2023), for instance, examined offloading decision‐making when an external store is limited in capacity or unreliable. Across three experiments, Murphy showed that participants tend to believe that external storage is more reliable than internal storage, and selectively offload high value information even when this strategy does not grant optimal utility.…”
Section: How Do Learning Memory and Metacognition Transform In Digita...mentioning
confidence: 99%
“…Both Murphy (2023) and Tsai et al (2023) examine individuals making decisions about whether to store to-be-remembered information internally or externally. Murphy presented individuals with a capacity limited external memory store (i.e., participants could "save" a subset of items in a memory task) while manipulating the value of to-be-remembered items, external store availability, and the perceived reliability of that store.…”
Section: The Dawn Of a New Age Of Metacognition Research?mentioning
confidence: 99%
“…When considering monitoring and control in these technology‐rich cognitive environments, it may be useful to conceptualize external resources as proper targets of these metacognitive processes (Dunn et al, 2021). For example, Murphy (2023) demonstrated that individuals appear to monitor the reliability of their external memory stores and use that information to control their use of internal and external stores (see also Pereira et al, 2022) just as individuals use their own confidence in their memory to make such decisions (Gilbert, 2015; but see Tsai et al, 2023). In a similar vein, Stone and Storm (2021) demonstrated that individuals use the time it takes to retrieve information from an internet search (i.e., external retrieval fluency) as a cue in predicting their ability to recall that information at a later point in time, similar to how individuals use the time to retrieve information from memory (i.e., internal retrieval fluency) to make similar judgments (Benjamin et al, 1998).…”
Section: The Dawn Of a New Age Of Metacognition Research?mentioning
confidence: 99%